2012
DOI: 10.2174/1874205x01206010113
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Infectious or Inflammatory Psychosyndromes

Abstract: Before an outline of the process of diagnosis and differential diagnosis in infectious and/or inflammatory psy-chosyndromes is given, a more general overview onto the approach to organic psychosyndromes seems useful, because in both entities similar principles of causality conclusion are applied. Correlation does not demonstrate causality. Therefore the principles and consensus recommendations, and limitations of causal inference to categorize psychosyndromes as be-ing ‘organic’, is to be discussed in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Our previous research investigated low level neuroinflammation (LLNI) subgroups in severe psychiatric disorders ( 4 ). Affective and schizophrenia spectrum disorders may be accompanied by pain and other sensory symptoms ( 5 ), which could be explained at least in part by LLNI pathomechanisms that arise from an interaction between CSF and peripheral nerves along the PCOP. It is also suggested that PCOP-associated symptoms prevail in classic neuroinflammation and possibly even in systemic inflammation ( 6 ).…”
Section: Introduction: the Peripheral Csf Outflow Pathways (Pcop)mentioning
confidence: 99%
“…Our previous research investigated low level neuroinflammation (LLNI) subgroups in severe psychiatric disorders ( 4 ). Affective and schizophrenia spectrum disorders may be accompanied by pain and other sensory symptoms ( 5 ), which could be explained at least in part by LLNI pathomechanisms that arise from an interaction between CSF and peripheral nerves along the PCOP. It is also suggested that PCOP-associated symptoms prevail in classic neuroinflammation and possibly even in systemic inflammation ( 6 ).…”
Section: Introduction: the Peripheral Csf Outflow Pathways (Pcop)mentioning
confidence: 99%
“…40,41 The relative success of using CSF filtration in treatment of psychiatric disease, neuroinflammatory disorders and chronic pain syndromes is based on the concept that CSF carries and transport antigens, not only centrally, but also along cranial and peripheral nerves; and the antigens triggers an immune response clinically expressed as mild `encephalitis' or pain and/or may be involved in pathophysiology by peripheral nerve-CSF signaling interactions. 42,43 The outflow pathways of CSF that are implicated in mediating the immunological CSN disease process are perfectly described in Quincke's study. 1 Quinke characterizes in detail the CSF outflow (via cinnabar deposits) along cranial nerves, intercostal nerves, lumbar and sacral nerves.…”
mentioning
confidence: 87%
“…Chronic encephalitis presents—with regard to the clinical picture—similarly to acute encephalitis, with the course just being protracted a priori , possibly with dominating or exclusive psychiatric symptoms in extended early stages of the disease. Respective psychiatric syndromes are typically unspecific, i.e., various and variant, though some symptom characteristics may be found, especially when including systemic signs and findings (14, 15).…”
Section: Critical Outline Of Terms In Clinical Use Around Neuroinflammentioning
confidence: 99%